Efficacy of seed dressing agents against root rot (Rhizoctonia solani) of mothbean (Vigna aconitifolia) - S.M. CHAUDHARI, D.B. PATEL*, NARENDRA SINGH and (Indian Phytopathology, 2016)
An experiment was conducted at Centre of Excellence for Research on Pulses, S.D. Agricultural University, Sardarkrushinagar, Gujarat during Kharif seasons of 2009 to 2014 to find out effective management of root rot disease of mothbean. The experiment was conducted on cv. GMO-2 with nine seed dressing agents viz, Carbendazim, Mancozeb, Carbendazim + Mancozeb combination, Thiram, Captan, Carboxin + Thiram combination, Vitavax, Trichoderma harzianum and cow dung against the disease caused by Rhizoctonia solani and compared with an untreated control. All the treatments were found effective in controlling the disease. However, the minimum root rot disease incidence was recorded in the seed treatment with combination fungicide Carboxin 37.5% + Thiram 37.5% WS @ 3 g/kg seed (9.14 %) followed by Captan 50 % WP @ 2 g/kg seed (10.28 %). The yield data revealed that the highest grain yield was recorded in the same seed treatment with combination fungicide Carboxin 37.5% + Thiram 37.5% WS @ 3 g/kg (547.97 kg/ha) followed by Captan @ 2 g/kg (510.08 kg/ha). Combination of fungicide Carbendazim 12% + Mancozeb 63% WP @ 3 g/kg seed treatment yielded 481.97 kg/ha and Carbendazim alone @ 3 g/kg seed yielded 478.49 kg/ha. The highest ICBR was obtained in the same seed treatment of combination fungicide Carboxin 37.5% + Thiram 37.5% WS @ 3 g/kg seed (1: 114. 60) followed by Captan 50% WP @ 2 g/kg seed (1: 110. 60). These treatments can provide an effective and economical management of root rot of mothbean.